Excessive Weight Gain Followed by Catch-Down in Exclusively Breastfed Infants: An Exploratory Study - Larsson, Melanie W. (Nutrients, 2018)
Some infants experience excessive weight gain (EWG) during exclusive breastfeeding, but causes and consequences are unknown. The objective was to identify factors associated with early EWG. Infants with EWG (HW-group) were examined at 5, 9 and 18 mo and compared to a breastfed group with normal weight gain (NW-group). Anthropometry, body composition, milk and blood samples, and milk intake were measured. Mean body-mass-index-for-age z-scores (BAZ) increased 1.93 from birth to 5 mo in the HW-group (n = 13) while the NW-group (n = 17) was unchanged (−0.01). The HW-group had 70% more fat mass at 5 mo, and then showed marked catch-down in BAZ from 5 to 18 mo (−0.84). Milk intake at 5–6 mo did not differ between the groups. In the HW-group milk-leptin was lower at 5 mo and serum-leptin was considerably higher at 5 and 9 mo compared to the NW-group. Serum-leptin at 5 mo was positively associated with weight-for-age z-score (WAZ) and fat mass and negatively with WAZ change from 5 to 9 mo. In conclusion, breastfed infants with EWG had catch-down growth when other foods were introduced. Low milk-leptin in the HW-group may have stimulated appetite and milk intake when weight gain was high. High serum-leptin in the HW-group suggests early leptin resistance, which could impact cerebral regulation of energy intake. Larger studies are needed to confirm these results.